2012
DOI: 10.1155/2012/984060
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Pain, Function and Radiographic Findings in Osteoarthritis of the Knee: A Cross-Sectional Study

Abstract: Objectives. The aim of this study was to investigate the relationships between pain, disability, and radiographic findings in patients with knee osteoarthritis (OA). Patients and Methods. A total of 114 patients with knee OA who attended the physical medicine and rehabilitation outpatient clinic were included in this study. The diagnosis was based on the American College of Rheumatology (ACR) criteria for knee OA. Age, duration of disease, and body mass index (BMI) of the patients were recorded. Radiographic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
84
6
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 25 publications
16
84
6
7
Order By: Relevance
“…This was in agreement with previous studies [26][27][28] and may be attributed to the difference between knee OA activity and severity parameters. 29 Also, such discrepancy was found between the grades of the proposed US scale for knee OA severity and disease activity parameters.…”
Section: Discussionsupporting
confidence: 93%
“…This was in agreement with previous studies [26][27][28] and may be attributed to the difference between knee OA activity and severity parameters. 29 Also, such discrepancy was found between the grades of the proposed US scale for knee OA severity and disease activity parameters.…”
Section: Discussionsupporting
confidence: 93%
“…Çalış-mamızdan farklı olarak bazı çalışmalarda, yaşın ve VKİ'nin öz-etkililik düzeyini etkileyen önemli faktör-ler olduğu belirtilmiştir. [24,25] Çalışmamızda OA'lı bireylerin VAS puan ortalamaları [27] Bu çalış-maların sonuçları bulgularımızı destekler niteliktedir.…”
Section: Pain a Riunclassified
“…Cubukcu et al (43) assessed 114 patients with knee osteoarthritis and concluded that pain, rigidity and duration of the disease affect the patients' functional incapacity. Observing our results, pain reduction and expansion of ROM were proportional among groups, except for the CO group that reported no significant difference between ROM degree before and after therapy.…”
Section: Discussionmentioning
confidence: 99%